Pengaruh Profesionalisme dan Disiplin Kerja Guru Terhadap Mutu Lulusan di Sekolah Dasar - Lusiana, Lusiana; Mu'in, Juhri Abdul; Siswoyo, Siswoyo; Adiputra, Sofwan (Universitas Muhammadiyah Magelang, 2026)
This research is motivated by the importance of graduate quality as an indicator of educational success, which is influenced by teacher professionalism and work discipline at Elementary Schools in Gugus 4, Ulu Belu District. The purpose of this study is to analyze the influence of teacher professionalism and work discipline, both partially and simultaneously, on the quality of graduates. This study employed a quantitative method with an ex-post facto approach, involving a sample of 51 respondents selected through a total sampling technique. Data were collected using questionnaires that had been validated and tested for reliability, and then analyzed using multiple linear regression via the SPSS program. The results showed that, partially, teacher professionalism has a positive and significant effect on the quality of graduates with a significance value of 0.001 < 0.05. Similarly, teacher work discipline partially has a positive and significant effect on the quality of graduates with a significance value of 0.001 < 0.05. Simultaneously, both variables significantly influence the quality of graduates with a contribution of 99.5%, while the remaining is influenced by other factors. The study concludes that improving the quality of graduates at Elementary Schools in Gugus 4, Ulu Belu District can be optimally achieved through strengthening professional competence and consistent enforcement of teacher work discipline.